ADMINISTRATIVE AND LEGAL PRINCIPLES OF THE ORIGIN OF APPRAISAL ACTIVITY IN THE WORLD, ITS DEVELOPMENT AND CURRENT STATE - Grinchuk, Alisa (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: to analyze the emergence of the concept of “evaluation activity” in society, to consider its historical development, to determine its essence and content, as well as the need for the existence of evaluation activity and its impact on legal relations in the property sector. Research methods: in the research process, the methods of systemic analysis and synthesis, historical and comparative, generalization and modeling, as well as dialectical and formal logic were used. Results: the historical aspects of the emergence and development of evaluation activity in the world and the main features of such activity are determined. The growth of the importance of evaluation activity is shown, and the factors that influenced its development are analyzed. The need for the emergence of evaluation activity is schematically determined as one of the main features of regulating social relations in the property sector. The results of the specified activity to date and certain problems that arise in the implementation of evaluation activity are considered. Discussion: the position is argued that evaluation activity is important in the property sector, change of owners and other actions to regulate social legal relations. The definition of evaluation, legal regulation of evaluation activities, subjects of evaluation activities, subjects of evaluation are proposed.